1999
DOI: 10.1046/j.1365-2958.1999.01311.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid residue Ala‐62 in the FimH fimbrial adhesin is critical for the adhesiveness of meningitis‐associated Escherichia coli to collagens

Abstract: SummaryAdhesion of meningitis-associated Escherichia coli O18acK1H7 to collagens was characterized. The E. coli strain IHE 3034 adhered to type IV and type I collagens but not to type III collagen immobilized on glass. Collagens lack terminal mannosyl units, yet the bacterial adhesion was completely abolished in the presence of ␣-methyl-D-mannoside. A cat cassette was introduced into the fimA gene of IHE 3034, and the resulting mutant strain IHE 3034-2 failed to adhere to collagens. In contrast, insertion of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 66 publications
4
73
0
1
Order By: Relevance
“…Surprisingly, in vivo, the A62S-ON strain (compared to a wt-ON control strain) rescued the CFUs/bladder phenotype at 24 hpi seen with the A62S mutant. Therefore, the in vitro mannose-binding defect of A62S is a result of altered FimH function (36,48), while the in vivo fitness defect of A62S is due to altered fim regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, in vivo, the A62S-ON strain (compared to a wt-ON control strain) rescued the CFUs/bladder phenotype at 24 hpi seen with the A62S mutant. Therefore, the in vitro mannose-binding defect of A62S is a result of altered FimH function (36,48), while the in vivo fitness defect of A62S is due to altered fim regulation.…”
Section: Discussionmentioning
confidence: 99%
“…None of the PSAA was located near the conserved mannose-binding pocket of FimH, and examination of the crystal structure of the FimC-FimH-mannose complex revealed no obvious relationship between PSAA mutations and mannose binding. Allosteric effects of FimH mutations have been described and may account for the decreased mannose binding of the A62S mutant (36,48). However, no structural basis for the severe in vivo fitness defect of the A27V/V163A double mutation is apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Pouttu et al [16] demonstrated that the presence of a serine at position 62 of the mature FimH (instead of alanine) completely abolishes binding of E. coli to collagen. All investigated APEC strains and the human AF288194 strain showed a serine at position 62 that could correspond to a lack of collagen binding.…”
Section: Discussionmentioning
confidence: 99%
“…The FimH adhesin has been described to be conserved throughout several strains of E. coli and even other F1 fimbriated Enterobacteriaceae [2]. Several important amino acids in the protein have been identified and extensively analysed [16,20,21]. On the contrary, the FimA major protein has been reported to be variable between the different strains of E. coli [2].…”
Section: Introductionmentioning
confidence: 99%
“…These point mutations may lead to truncations or frameshifts in genes that may play a role in host-pathogen interactions. Finally, the role of point mutations that change the amino acid sequence of a protein should also be considered, as it has been shown that a single amino acid change in the E. coli FimH adhesin leads to loss of collagen-binding activity (20). Some of the variable surface proteins identified in the comparative genome analysis of B. suis and B. melitensis, therefore, may be additional candidates for host-specific virulence factors.…”
mentioning
confidence: 99%